Infrastructure-less Vehicular Communication System Using Li-Fi Technology - Gupta, Mahima; Sharma, Saumya (International Journal of Computer (IJC), 2016)
This paper introduces vehicle to vehicle (v2v) communication system using Li-Fi technology. The lightning quick transfer of information between vehicles becomes mandatory when danger is imminent as it can instantly diffuse a potentially hazardous situation. Connected cars will help cities and states cut down on congestion and improve safety. On the road, cars will communicate with each other, automatically transmitting data such as speed, position, and direction, and send alerts to each other if a crash seems imminent. We consider the several scenarios: 1) communication between car and RSU 2) inter vehicular communication 3) communication based network system. The reach ability, delay in transmission and percentage collisions are evaluated with respect to the average distance between cars using pixel oriented visualization. With the help of LEDs fitted in the car, we can transmit data seamlessly using rapid pulse of light over VANET (Vehicular Ad-hoc network) for high speed communications.